Effect of Combination of Calcium Hydroxide and 2% Chlorhexidine Gel as Intracanal Medications in Comparison to Calcium Hydroxide Paste on Postoperative Pain and Bacterial Endotoxins in Necrotic Teeth: Randomized Clinical Trial - Yasser Hendy; Geraldine Ahmed; Hany Sadek; Rania Khatab (Ain Shams University, Faculty of Dentistry, 2024)
AbstractAim: Assessment of post-operative pain and quantification of bacterial endotoxins in adult patients suffering from necrotic pulp condition with chronic periapical periodontitis by using calcium hydroxide paste intracanal medication with 2% chlorhexidine gel, Calcium hydroxide paste intracanal medication only and with mechanical preparation without intracanal medications.Methods: Forty five patients with single rooted teeth suffering from necrotic pulp status were divided into 3 groups (n=15), the first group received mechanical preparation only , the second group received calcium hydroxide intracanal medication only, while the third group received mixture of calcium hydroxide and 2 % chlorhexidene gel intracanal medication. Numerical rating scale was used to assess the pain experience post operatively while chromogenic end point Limulus Amebocyte Lysate assay (LONZA) was used to quantify the amount of endotoxins. Results: Calcium hydroxide was superior in decreasing the postoperative pain at time interval 4 hours and 24 hours in comparison to the mixture of calcium hydroxide paste and 2 % chlorhexidene gel significantly, while the mixture was better to reduce the endotoxins with statistically insignificant value.Conclusion: Using one of the intracanal medications for 2 week time interval in necrotic teeth can help to allivate postoperative pain and reduce endotoxins.